Prevalence of defining malignancies in adult patients with HIV/AIDS in the National Cancer Institute of Colombia. 2007-2014 (2017)
Introduction: The widespread use of antiretroviral therapy has increased the survival rates of patients infected with human immunodeficiency virus (HIV) and, in consequence, the prevalence of both defining and non-defining cancers. In Colombia, information in this regard is unknown.Objective: To determine the prevalence of defining malignancies in adult patients with HIV treated at the National Cancer Institute over a seven-year period.Materials and methods: Descriptive study involving adult patients diagnosed with HIV and cancer. Sociodemographic variables, CD4 count, viral load and antiretroviral therapy were analyzed by establishing association measures with the presence of defining malignancies.Results: 139 patients with confirmed HIV and cancer diagnosis were found; 84.2% were men. The age range was between 18 and 71 years, with a mean of 41.3±10.9 years. Defining cancers corresponded to 65.5% of the cases, the most frequent being non-Hodgkin lymphoma. The remaining percentage corresponded to non-defining cancers, mainly anal cancer and Hodgkin’s lymphoma.Conclusion: Despite the global trend, the population studied here shows predominance of defining cancers, which, like HIV, continue to be detected at a late stage.